The underlying dimensions of relationship marketing in the Malaysian mobile service sector. - Bojei, Jamil; Radam, Alias; Abu, Mimi Liana (2012)
After so many years, the Malaysian mobile service market is getting saturated whereby the service operators had difficulties to differentiate themselves since they had offered almost the same services. As the service options are wide, therefore customers become less committed to a particular provider and might easily shift from one operator to another. This situation forces the service providers to create a strategy that focuses more on gaining and retaining long term relationship with their customers. Therefore, the objective of this study is to determine the underlying dimensions of relationship marketing in the Malaysian mobile service sector. A sample of 300 customers is drawn using Mall Intercept Scientific Procedures around Klang Valley and the Structural Equation Model (SEM) is utilized in testing the proposed model. The results show that the relationship between the exogenous latent factors and the overall endogenous factor are significant ranging from 0.77 to 0.94. That is, relatively high proportion of the variance in relationship marketing are well-explained by each of the factors.